A 0.026 mm(2) Time Domain CMOS Temperature Sensor with Simple Current Source - Park, Sangwoo (Micromachines (Basel), 2020)
This paper presents a time domain CMOS temperature sensor with a simple current source. This sensor chip only occupies a small active die area of 0.026 mm(2) because it adopts a simple current source consisting of an n-type poly resistor and a PMOS transistor and a simple current controlled oscillator consisting of three current starved inverter delay cells. Although this current source is based on a simple architecture, it has better temperature linearity than the conventional approach that generates a temperature-dependent current through a poly resistor using a feedback loop. This temperature sensor is designed in a 0.18 μm 1P6M CMOS process. In the post-layout simulations, the temperature error was measured within a range from −1.0 to +0.7 °C over the temperature range of 0 to 100 °C after two point calibration was carried out at 20 and 80 °C, respectively. The temperature resolution was set as 0.32 °C and the temperature to digital conversion rate was 50 kHz. The energy efficiency is 1.4 nJ/sample and the supply voltage sensitivity is 0.077 °C/mV at 27 °C while the supply voltage varies from 1.65 to 1.95 V.